Distribution of Projects Financed Through the Regional Operational Programme in the Development Regions: South – Muntenia, Bucharest – Ilfov, South – Eastand North - East - Anamaria - Cătălina RADU; Andra - Ileana DOBRESCU; Maria - Cristina MITRICĂ (PĂDURE) (Revista de Management Comparat International)
In the period 2007-2013, several projects were submitted through the Regional Operational Programme that targeted the objectives laid down by it. The priority axes aimed to support the sustainable development of cities, the improvement of the transport infrastructure and social services, the support of business development, and tourism sustainable development and promotion. This paper aims to analyze the projects submitted by the Regional Operational Programme in four development regions, namely South – Muntenia, Bucharest – Ilfov, South – East and North – East. The analysis was based on the statistical data available at this time on the official websites of the Regional Development Agencies in each region mentioned above. The research was conducted from May 1 to May 20, 2015